Pengaruh Perendaman Benih dengan Air dan Air Cucian Beras pada Pertumbuhan Benih Kopi (Coffea sp.) - Budiawan, Rista; Same, Made; Hartono, Joko S. S. (Politeknik Negeri Lampung, 2023)
Coffee seeds are an important planting material in coffee cultivation. Coffee germination is a complex process. One of the efforts to germinate coffee seeds is by soaking the seeds in water. The purpose of this study was to determine the effect of the length of time soaking seeds in water on the germination of coffee seeds, knowing the effect of the length of time soaking in rice washing water on the germination of coffee seeds, and knowing the interaction between soaking with water and soaking with rice washing water on coffee seed germination. This study used a factorial randomized block design (RBD) with two factors, and was repeated three times. The results showed that water immersion had no effect on coffee seed germination, rice water immersion for 6 hours had an effect on plant height at planting age of 4 WAP and 11 WAP, and there was an interaction between water immersion time and rice water immersion time at 12 WAP planting age. The best combination is 12 hours of water immersion + 12 hours of rice washing water on wet weight of shoot and dry weight of shoot.